Analysis of The Study of The Supervision of Nursing Room In The Implementation of Nursing Supervision - Kustiati, Etik; Pohan, Vivi Yosafianti; Hartiti, Tri (South East Asia Nursing Research, 2020)
Preparaing rooms for covid 19 patients must be supported by the availability of superior human resources and good nursing management functions. Nursing care given to Covid 19 patients must be complete and well documented. The quality of service needs to be monitored on an ongoing basis by optimizing the supervisory function of the head of the room and the orphans by means of nursing supervision. The purpose of this analysis is to determine the usefulness of the nursing room supervision function in this case by implementing nursing supervision. The use of the action method in this analysis aims to develop new skills or new approaches and be applied directly and studied the results. The assessment using eight nursing management functions carried out in Sulaiman 4 room Roemani Muhammadiyah Semarang Hospital found that the most priority problems were not optimal in the implementation of the supervisory activities of the head of the room and head of the team. The supervision activities in the Sulaiman 4 room have actually been carried out but have not been scheduled and well documented. Actions taken by refreshing the nursing supervision through Small Group Discus activities, preparation of supervision schedules and making supervision formats. Evaluation of the actions taken, SGD was attended by 19 participants consisting of 15 nurses Sulaiman 4 and four other inpatient heads, the supervision schedule was made according to the agreement of the Head of the Room and the Head of the Team. The direct supervision format was used in Sulaiman 4 room according to the predetermined schedule, namely on December 11, 2020. The results achieved from the supervision obtained a significant increase in the number of completeness of nursing documentation from 48.24% to 82.98%.